Effects of organic medium on growth and root formation of Cinchona ledgeriana Moens planting material at early stage of nursery - Dalimoenthe, Salwa Lubnan (Research Institute for Tea and Cinchona, 2014)
Cinchona plants commonly propagated through vegetative propagation using grafting between scion and rootstocks and planting on mixed of top soil and sub soil. To overcome these problems, an alternative planting medium of cinchona seedling has to be explored to reduce the use of soil. In this research, various organic materials have been tested to see their effect on growth and root formation of cinchona seedling at early stage of cinchona nursery. The experiment was arranged in a randomized complete design (RCD) with 17 treatments, each treatment consists 20 plants/replication. Treatments tested were combination of organic matter (cocopith, rice husk, sawdust and peat soil) with top soil (15% and 25%). Cow dung or seaweed, as organic fertilizer was added to enrich planting medium. Results shows that cocopith, rice husk, sawdust and peat soil enriched with cow dung or seaweed has no significance difference with top soil medium (conventional planting medium) on plants living percentage, plants height, leaves number and, stem diameter of cinchona seedlings at early stage of cinchona nursery comparing with the conventional way. On plants heights and leaves number, there are significant difference caused by the treatment during three months after plantings. The number of rooting plants in between 33% up to 100%. In general, plants regeneration and compatibility between scion and rootstock of cinchona tested plants shows that the cell regeneration or cell growths are well and there is no sign on incompatibility between scion and rootstock.